Research Trend of Inquiry Learning in Elementary School in the Last 10 Years: To Determine the Opportunities in the Future - Rahyu Setiani (Indonesia Approach Education, 2023)
Inquiry Learning in Elementary School research has evolved in the last ten years, making it an interesting topic to research to understand the trends and developments of Inquiry Learning in Elementary School so that it becomes a research opportunity. This study aims to analyze research trends, researchers' contributions, and the most researched research topics on the topic of Inquiry in Elementary School in education over the past ten years and identify potential research topics related to Inquiry in Elementary School in Education in the future. This study uses the bibliometric analysis method using Google Scholar database and Software VOSviewer, where 138,000 articles were obtained. The results of the bibliometric analysis show that Inquiry Learning in Elementary School research has experienced a consistent decline in the last ten years. This becomes the next challenge, and opportunity for future research. Further research related to Inquiry Learning in Elementary School can be used and applied with a STEM-based approach namely Science, technology, engineering, and mathematics. This is because the stem-based Inquiry model can improve students' critical thinking and problem-solving skills. This study has limitations, namely only using one database, Google Scholar, to obtain research data. Therefore, it is recommended that Inquiry Learning in Elementary School research be carried out using other databases besides Google Scholar to obtain more extensive data.